Determination of the Initial Abnormal Discharge Site in Temporal Lobe Epilepsy Through Combined EEG and Neuroimaging. What Is Next? - Rentería-Palomo, Ana A.; Montes-Ochoa, Jose L.; Martinez-Mayorga, Adriana; Reyes-Vaca, Jorge Guillermo; Rodríguez-Leyva, Ildefonso (Frontiers in Neurology, 2021)
Objective To determine the relationship between atrophy of the hippocampus and severity of epilepsy in patients with temporal lobe epilepsy (TLE) as the first step to evaluate the surgery of epilepsy possibility. In addition, to analyse why these patients cannot be taken to epilepsy surgery. Methods Volumetric MRI of the hippocampus was performed in 51 consecutive patients (25 men; mean age 40) with TLE. TLE diagnosis, lateralisation, and severity (mild, moderate, severe) of seizures were based on a comprehensive evaluation including neurologic examination and EEG in all patients. Patients with evidence of a lesion other than hippocampal sclerosis were not included in the study. We assessed the relation between hippocampal volumes and electrophysiological evidence of seizure severity. Results According affected side based on the EEG found a statistically significant difference (p < 0.001) in volume and a positive correlation between epilepsy and hippocampal atrophy. Conclusion Our results confirm that volume loss to the hippocampus in patients with TLE correlates with the severity of epilepsy based on EEG. Therefore, surgical treatment is considered early when hippocampal atrophy is evident in patients with refractory TLE. However, in our countries, it is a challenge to get a patient to epilepsy surgery. Therefore, we try to analyse the situation in our hospitals.